Atopic dermatitis is not associated with actinic keratosis: cross‐sectional results from the Rotterdam study. (1st July 2016) - Hajdarbegovic, E.; Blom, H.; Verkouteren, J.A.C.; Hofman, A.; Hollestein, L.M.; Nijsten, T.
Summary: Background: Epidermal barrier impairment and an altered immune system in atopic dermatitis (AD) may predispose to ultraviolet‐induced DNA damage. Objectives: To study the association between AD and actinic keratosis (AK) in a population‐based cross‐sectional study. Methods: AD was defined by modified criteria of the U.K. working party's diagnostic criteria. AKs were diagnosed by physicians during a full‐body skin examination, and keratinocyte cancers were identified via linkage to the national pathology database. The results were analysed in adjusted multivariable and multinomial models. Results: A lower proportion of subjects with AD had AKs than those without AD: 16% vs. 24%, P = 0·002; unadjusted odds ratio (OR) 0·60, 95% confidence interval (CI) 0·42–0·83; adjusted OR 0·74, 95% CI 0·51–1·05; fully adjusted OR 0·69, 95% CI 0·47–1·07. In a multinomial model patients with AD were less likely to have ≥ 10 AKs (adjusted OR 0·28, 95% CI 0·09–0·90). No effect of AD on basal cell carcinoma or squamous cell carcinoma was found: adjusted OR 0·71, 95% CI 0·41–1·24 and adjusted OR 1·54, 95% CI 0·66–3·62, respectively. Conclusions: AD in community‐dwelling patients is not associated with AK.